Cooperativas habitacionais em Goiânia e o programa habitacional Minha Casa Minha Vida - Azevedo, Janamaina Costa Bezerra de (2013)
The issue of housing can be considered, at present, one of the main social problems of urban Brazil. A view that sees the problem of housing built to the question of the right to the city, you can see that the claims in relation to housing in various facets emerge: solution to the serious problems of infrastructure (sanitation, paving, etc.), housing to address the alarming number of families without their own homes and questioning of urbanization in peripheral areas and slums. Methodology will be done through interviews and questionnaires investigative, analytical and exploratory way. It is important to understand how current urban problems, especially those related to housing, reflecting a century of policies that have not considered the poorest or, in some periods, even existed. In this sense, becomes a resumption relevant historical question of urban housing in Brazil, highlighting some policies and projects of the state to state to try to address this social issue. This dissertation presents these issues in the analysis of housing cooperatives in Brazil and in the city of Goiania amid the granting of benefits from the federal government on housing plan for the period 1986 to 2010, focusing on the new housing Programa Minha Casa, Minha Vida. The program of the Federal Government that even bringing the whole range of property speculation had a considerable advance on the issue of housing.